Natural Emergencies Occurring in the Mountains Districts of the Republic of Uzbekistan and Their Economic Impact on Ring Farm Structures, Railway Sections (Eurasian Journal of Engineering and Technology, 2022)
In this article the mountainous districts of our republic and the city who are in the flood, economic and transport them to think about the impact to the facilities of the nation. In the article about the effects of the flood of the nation's economic sheet provides a photo to the object. Knowledge about the effects of flooding and other agricultural buildings are given. Along with suggestions about measures to combat the effects of the flood, so the flow will be given